Multi-Phases Fluid Activity Characteristics of Longmaxi Formation and Its Impact on Resistivity in the Changning Area, Southern Sichuan Basin, Southwest China - Cui, Yue; Li, Xizhe; Han, Lingling; Feng, Yong; Guo, Wei; Lin, Wei; Qian, Chao; Feng, Tao (Frontiers in Earth Science, 2022)
Wells with low gas content and low resistivity in the Changning area, southern Sichuan Basin were selected for this study. The burial-thermal history was reconstructed, and the characteristics of multi-phase fluid activity was clarified using microscopic observation and testing of fluid inclusions in the Longmaxi shale fracture veins. Compared with wells with a high gas content and high resistivity, the influence of fluid activity on resistivity was analyzed. The results show that the thermal evolution of the bituminous inclusions trapped in the veins has reached the stage of carbonaceous-metamorphic bitumen, and the organic matter is fully cracked for gas generation, with some exhibiting the phenomenon of "graphitization". The synchronous fluid with bitumen was existed due to shallow burial with a middle-low maturity stage for about 280 and 292Ma. Two phases of fluids were existed in the deep burial stage, thus maturing for about 103 Ma, and the uplift stage at about 28 Ma and 32 Ma, with high homogenization temperatures (Th) (varying from 185 to 195 ℃ and 165 to 180 ℃). The corresponding pressure coefficients varied between 1.67 and 2.09, 1.56 and 1.92 in a moderate-strong high pressure state. The last two phases of fluid formation in the late uplift stage for about 4 to 19Ma and 6 to 10Ma were characterized by low salinity at medium-low Th (varied from 140 to 155 ℃ and 120 to 135 ℃), with pressures of 57.47 to 74.50MPa and 51.44 to 59.41MPa (pressure coefficients of 1.09 to 1.41 and 1.18 to 1.37), in an atmospheric-weak overpressure state. In the initial uplift stage after deep burial, the fluid closure in the Changning area was good. In contrast, the wells with low gas content are because of the strong tectonic forces causing the shale gas to be released, and caused by the multi-phase fluid activity during the late uplift stage. New evidence indicates that the emergence of low resistance in the localized Changning area is not only related to the high degree of evolution of organic matter, but is also affected by the multi-phase fluid modification in the late uplift stage.